A Review of Various Power Management Schemesin HEV - Sahu, Atman Raj; Bose, Bibaswan; Kumar, Shubham; Tayal, V.K. (2020 8th International Conference on Reliability, Infocom Technologies and Optimization (Trends and Future Directions) (ICRITO), 2020)
The generation of HEV has already arrived and will live for many ages. Hybrid vehicles comprises of multiple energy sources just because to match the performance demands and has vast advantages such as reducing air pollution, fuel depletion and emission reduction. In order to provide better efficiency power management plays a vital role in HEV. There are many intelligent power management techniques that can achieve optimal power handling which are suitable for real time application and can provide better efficiency for different driving condition. We will basically study on Rule based methods and optimization based methods. In rule-based methods, methods are easily implemented and is very simple in real time but cannot provide best of optimality whereas in optimized based methods, it can provide better optimal results but it all comes with the cost of high computational requirements and price. Thus, in this review-based paper we will brief about the latest trends of power management strategies that are based upon rule based and optimization based and will highlight on which one will yield better optimal results with its pros and cons.